Digital Literacy in Formal Online Education: A Short Review - Yustika, Gaung Perwira; Iswati, Sri (Dinamika Pendidikan, 2020)
This study aims to explain the current findings of digital literacy in formal online education. The methods of research is a type of library description obtained from relevant scientific articles obtained from internet search media library engines: proquest, researchgate, google scholar and other search engines with keyword search "digital literacy" to find the publication of related scientific papers / relevant to the topic. Then the 41 articles found (listed in the references) are studied and then explained from the author's perspective. Digital literacy is multi-dimensional, built by multi construct hypotesis. In the previous research found a higher level of digital literacy that was positively related to the output of learning outcomes in the subjects studied. Online learners feel anxious because they do not understand and are accustomed to online classes, especially for those who have limited computer skills. Most importantly, independent students get the final grade of the program far better than non-independent students. The best predictor of academic success, measured by the final grades, namely components of academic skills, reading and writing abilities. Higher levels of digital literacy positively affected the high output of learning outcomes to student academic performance.